(untitled) (Annals of Bangladesh Agriculture, 2021)
A field experiment was conducted to investigate the effect of organic and inorganic fertilizers on growth, yield and physio-chemical properties of papaya (Carica papaya) from February to December 2019. The experiment was designed into twelve treatments [T1 = Control, T2 = 100% RDF (Recommended Dose of Fertilizers), T3 = 50% RDF+ 50% MOC (Mustard Oil Cake), T4 = 50% RDF+ 50% VER (Vermicompost), T5 = 50% RDF + 50% PM (Poultry Manure), T6 = 25% RDF+ 75% MOC, T7 = 25% RDF + 75% VER, T8 = 25% RDF+ 75% PM, T9 = 100% MOC, T10 = 100% VER, T11 = 100% PM and T12 = MOC + VER + PM] at the experimental field of Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur. The experiment was laid out in randomized complete block design with three replications. The effect of treatments varied significantly for most of the characters studied. Results showed that the plant growth, yield contributing traits, fruit yield and quality of papaya significantly increased in T10 treatment compared to other treatments. The maximum amount of dry matter of fruit (4.37%), TSS (18.17 %), total sugar (9.43 g/ 100g), reducing sugar (6.34 g/ 100g), β- carotene (0.24 mg/ 100g), mineral as Ca (0.39%), Mg (0.33%) and K (2.08%) were found in T10 treatment and the minimum amount were found in the control T1. The maximum amount of non-reducing sugar was obtained from T12 (3.93 g/ 100g) and the minimum from T3 (2.23 g/ 100g). Ascorbic acid was found maximum in T7 (24.99 mg/100g) and minimum from T11 (22.00 mg/100g). A significant influence of T10 treatment on growth, yield and physio-chemical characters was observed. The application of 100% vermicompost which influenced growth, yield and physio-chemical properties of papaya in Salna series of Red Brown-terrace soil is suggested. Ann. Bangladesh Agric. (2020) 24(2) : 69-83